THE ECONOMICS OF IḤTIKĀR - Suherman Rosyidi (Universitas Airlangga, 2018)
AbstracsIḥtikār is not a new problem in Islamic economics. The Prophet (peace be upon him) himself firmly stated that the perpetrator of iḥtikār are sinners. Nevertheless, Islamic thinkers, since the very beginning, not one voice in understanding this issue, both its meaning and the type of goods concerned. Among the modern Islamic economists, some interpret iḥtikār as monopoly, and some are simply declare it as an action of hoarding. They also not one voice in the matter of the type of goods hoarded; the majority stated that the goods that should not be hoarded is just food stuff alone, while others declare all items. This article will explain the issue.